1995
DOI: 10.1002/yea.320111003
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of heterologous membrane proteins into proliferated internal membranes in Saccharomyces cerevisiae

Abstract: Overproduction of chimeric proteins containing the HMG2/1 peptide, which comprises the seven transmembrane domains of Saccharomyces cerevisiae 3-hydroxy-3-methylglutaryl-CoA reductase isozymes 1 and 2, has previously been observed to induce the proliferation of internal endoplasmic reticulum-like membranes. In order to exploit this amplified membrane surface area for the accommodation of heterologous microsomal proteins, we fused sequences coding for human cytochrome P4501A1 (CYP1A1) to sequences encoding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Kim et al previously reported that overexpressing INO2 could expand the ER, thus improve the capacity to synthesize ER-associated proteins and cytochrome P450-mediated PPD, and increase available space to accommodate them [ 20 ]. In our study, the cell growth and PPD production of BY-III strains are significantly improved by up-regulation INO2 possibly due to efficient localization of cytochrome P450 in an expanded ER as a possible mechanism, which is consistent with Kim’s studies [ 36 ].
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…Kim et al previously reported that overexpressing INO2 could expand the ER, thus improve the capacity to synthesize ER-associated proteins and cytochrome P450-mediated PPD, and increase available space to accommodate them [ 20 ]. In our study, the cell growth and PPD production of BY-III strains are significantly improved by up-regulation INO2 possibly due to efficient localization of cytochrome P450 in an expanded ER as a possible mechanism, which is consistent with Kim’s studies [ 36 ].
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…Strain YNW64 (MATa,trp5,cprl::ura3A5,ura3A5, derived from strain YES9 by disruption of the URA3 gene present in the cprl::URA3 alíele (Wittekindt et al, 1994).…”
Section: Strainsmentioning
confidence: 99%
“…In the second fusion protein (HMG2/1-AhOR-CYPlAl), the amino-terminal 47 amino acids that represent the membrane anchor domain of hOR are replaced by a chimera of the seven transmembrane domains of yeast HMG-CoA reducíase isozymes 1 and 2 (HMG2/1). Expression of fusion constructs between the HMG2/1 peptide and human CYP1A1 has previously been shown to induce proliferation of membranes of the endoplasmic reticulum and targeting of the enzymatically active fusion proteins into these membranes (Wittekindt et al, 1994). By analogy, the HMG2/l-AhOR-CYPlAl fusion protein is expected to be targeted into the proliferated membranes and to be stabilized by the yeast HMG2/1 peptide functioning as membrane anchor domain.…”
Section: Introductionmentioning
confidence: 97%